Pengaruh Sosial Media Marketing , Kualitas Produk & Kualitas Pelayanan Terhadap Keputusan Pembelian Konsumen Starbucks Kemang - Aldo Nugroho; Rully Arifiansyah (Panorama Nusantara, 2024)
The purpose of this research is to assess the influence of social media marketing, product quality, service quality on purchasing decisions at Starbuck Kemang. The Questionnaires were distributed to 130 respondents using accidental sampling. Data analysis was done using SmartPLS. The results of this analysis, there is a positive and significant influence of social media marketing on purchasing decisions, product quality has no effect on purchasing decisions and quality service has a positive and significant effect on purchasing decisions.